Pengaruh Beban Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Klinik Pratama Safubot Area Bekasi: The Effect of Workload and Work Motivation on Employee Performance at the Safubot Primary Clinic in the Bekasi Area - Juwita Marlina; Usran Masahere (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Employee performance is an important factor in supporting the quality of health services. High job demands can affect workload and work motivation, ultimately impacting performance. Safubot Pratama Clinic Bekasi Area has service characteristics with high work intensity in certain periods, so optimal human resource management is needed. This study aims to analyze the effect of workload and work motivation on employee performance at Safubot Pratama Clinic Bekasi Area. The research method used is a statistical quantitative method. Data collection was carried out by distributing questionnaires with a sample of 50 respondents. Data analysis techniques used were validity test, reliability test, multiple linear regression analysis, t test, and F test with the help of SPSS version 27 application. The results showed that workload had a positive and significant effect on employee performance, evidenced by the calculated t value of 3.207 which is greater than the t table of 1.677 and a significance value of 0.002 <0.05. Work motivation also has a positive and significant effect on employee performance with a calculated t value of 5.989 greater than the t table of 1.677 and a significance value of 0.001 < 0.05. Simultaneously, workload and work motivation have a significant effect on employee performance with a calculated F value of 18.926 greater than the F table of 3.19 and a significance value of 0.001 < 0.05.